Religious discourse in contemporary narrative in identity shaping - Sánchez Quirós, María Ángela (2014)
The patriarchal tradition inherited by the Roman Catholic religion is evidented in the contemporary literature in Latin America mainly in texts written by women, in which speeches influenced by a strong religious you can determiny the way of acting and thinking of female and male. Toward the middle of XX century latinamerican literature started to evidence social discomfort about the way gender was “lived” and transmited in their speeches which was full of inherited prejudice of occidental religious traditions that oppressed women and other sexual preferences while males become more and more powerfull. Next to this amazing situation female talent arises with questioning about patriarchal values discomfort generating new ways of view of the world, more inclusive and fair.